Development of large-fruited bird cherry cultivars on the basis of wild species for northern and eastern regions of Russia - V. S. Simagin; A. V. Lokteva (Труды по прикладной ботанике, генетике и селекции)
Bird cherry occupies a special place among stone fruit plants. Its fruits, collected in nature, were widely used by local communities, native to regions with severe climate. Development of new bird cherry cultivars, well adapted to such environments, with stable productivity and larger fruit, is a necessity.Crossings were performed involving the most large-fruited genotypes of Prunus padus L.  and P. virginiana L.,  selected during the study of their intraspecific variability and interspecific hybrids. A number of hybrids were identified for their considerably higher fruit weight than that of both parents. Crossing the most large-fruited hybrid cultivars ‘Pamyati Salamatova’ and ‘Cherny blesk’ with large-fruited P. padus samples from Bondarev No. 11-2-64, No. 11-2-70, No. 11-2-76, and P. virginiana samples No. 1-14-1 and No. 10-5-2, produced many hybrids with a fruit weight gain of 20–50% over the parent with the largest fruit. It can be explained by the polygenic nature of fruit weight inheritance. The samples with the largest fruits had an average fruit weight of 1.4–1.5 g and maximum weight of 1.8–1.9 g. Many of them combined large fruit size with good quality and high productivity. Brief descriptions of fruit traits are presented for several hybrids. Suppositions are made about the prospects of further breeding for the large fruit trait on the basis of the same genetic sources or with the use of other sources of large fruit size in hybridization.Thus, preliminary selection of the best genotypes in nature and in introduced populations, followed by their crossing within their own species and with other species, makes it possible to produce genotypes with larger fruits than the average fruit size for a population and considerably larger than in their parents. It would help to develop bird cherry cultivars, well adapted to local conditions, for amateur and industrial horticulture under different climate conditions of Russia.